1)c3h6+hoh(н+) =c3h7oh-получение
2c3h7oh+2na=2c3h7ona+h2
ch3-ch2-ch2oh+cuo(t) =ch3-ch2-coh+cu+h2o
2)сh3-ch2-ch2-ch2oh + cuo(t) =ch3-ch2-ch2-coh +cu+h2o-получение
ch3-ch2-ch2-coh+h2=ch3-ch2-ch2-ch2oh
ch3-ch2-ch2-coh+ag2o(t) = ch3-ch2-ch2-cooh+2ag
3)2ch3-(ch2)3-cooh+2na=2ch3-(ch2)3-coona+h2
2ch3-(ch2)3-cooh+mgo=(ch3-ch2-ch2-ch2-coo)2mg+h2o
ch3-(ch2)3-cooh+naoh=ch3-(ch2)3-coona+h2o
2ch3-(ch2)3-cooh+na2co3=2ch3-(ch2)3-coona+co2+h2o
4)c2h5oh+ch3-cooh= c2h5-o-co-ch3+h2o
c5h11oh+h-cooh= c5h11-o-co-h +h2o
c7h13oh+c2h5-cooh= c7h13-o-co-c2h5+h2o
c5h11oh+ c5h11-cooh=c5h11-o-co-c5h11+ h2o
{2у-3х=8
у=4-3х выразили из первого уравнения, подставляем во второе:
2*(4-3х)-3х=8
8-6х-3х=8
8-8=9х
9х=0
х=0 подставляем х в выраженое у из первого уравнения:
у= 4-3*0
у=4
ответ: (0;4)